Characterization of Soil Pores Through X-Ray Computed Microtomography and Carbon Mineralization Under Contrasting Tillage and Land Configurations in the Indo-Gangetic Plains of India - Ghosh, Tridiv; Maity, Pragati Pramanik; Das, T. K.; Krishnan, P.; Chakraborty, Debashis; Bhatia, Arti; Ray, Mrinmoy; Kundu, Aditi; Bhattacharyya, Ranjan (Frontiers in Environmental Science, 2022)
Contrasting tillage and land configuration have important roles in porosity and pore size distribution (PSD), which in turn affects the carbon mineralization in soil. Information on the effects of these treatments on PSD and subsequent carbon mineralization is very limited. Hence, an attempt was made to evaluate the long-term impact of soil tillage and land configurations on the distribution of soil pores and its relationship with soil carbon mineralization under a maize (Zea mays)-wheat (Triticum aestivum) rotation. There were five treatments, that is, conventional tillage, (CT); permanent broad bed, (PBB); PBB + residue (R); zero tillage, (ZT); and ZT + R. Soil pores were quantified by X-ray computed tomography (μ-CT). The conversion of CT to ZT and PBB with or without residue retention (+R) resulted in the reduction of pores >60 μm diameter and was mostly due to a reduction in the number of larger size macro-pores (>110 μm). This resulted in restricted drainage. However, under these practices, pores with larger diameters (60–110 μm) facilitated soil aeration. The total organic carbon (TOC) was 15–48% and 17–47% higher under PBB, PBB + R, ZT, and ZT + R than that under CT in the 0–5 and 5–15 cm layers. The highest MWD (1.01 mm) was in the plots under PBB + R, and the lowest was in the CT plots, and all residue-retained plots (ZT + R and PBB + R) had a higher MWD than residue removal plots (ZT and PBB). Relative to CT, soil C mineralization rates in 0–5 and 5–15 cm soil depths were 63 and 55% higher in the alternate tillage practices, respectively, and the highest value occurred in PPB + R treatments. Increased labile C concentrations were indicative of greater mineralization and were correlated with pores >60 μm, particularly in the size range 110–500 μm and TOC concentrations of 0–15 cm soil layer. Thus, the transition to alternate tillage from the conventional tillage enhanced soil organic carbon concentration (16–47.5%), improved soil structure, reduced the diameter of pores up to >60 μm, and facilitated C mineralization by altering the pore size distribution of soil under a maize-wheat system in the IGP.